2020
DOI: 10.1111/eci.13455
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte membrane fluidity as a marker of diabetic retinopathy in type 1 diabetes mellitus

Abstract: Background: A high level of glycosylated haemoglobin (HbA1c), which is a nonenzymatic glycosylation product, is correlated with an increased risk of developing microangiopathic complications in Diabetes Mellitus (DM). Erythrocyte membrane fluidity could provide a complementary index to monitor the development of complications since it is influenced by several hyperglycaemia-induced pathways and other independent risk factors. Materials and methods: 15 healthy controls and 33 patients with long-duration (≥20 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…NADH autofluorescence, excited at 740 nm, was acquired in the spectral emission range 425–475 nm. Contributions from cytoplasm and mitochondria, respectively, have been obtained separately by applying a machine learning-based pixel classification workflow through the open-source software Ilastik ( , accessed on 5 May 2022) [ 35 , 36 , 37 , 38 ]. The separation of the cytoplasmic and mitochondrial NAD(P)H responses through microscopy [ 39 ], perfectioned through time by optimizing acquisition and segmentation techniques, is nowadays a strong and reliable assessment of NAD(P)H redox state.…”
Section: Methodsmentioning
confidence: 99%
“…NADH autofluorescence, excited at 740 nm, was acquired in the spectral emission range 425–475 nm. Contributions from cytoplasm and mitochondria, respectively, have been obtained separately by applying a machine learning-based pixel classification workflow through the open-source software Ilastik ( , accessed on 5 May 2022) [ 35 , 36 , 37 , 38 ]. The separation of the cytoplasmic and mitochondrial NAD(P)H responses through microscopy [ 39 ], perfectioned through time by optimizing acquisition and segmentation techniques, is nowadays a strong and reliable assessment of NAD(P)H redox state.…”
Section: Methodsmentioning
confidence: 99%
“…Cordelli's study [ 40 ] found that erythrocyte liquidity could be used as an auxiliary indicator to analyze the progression of diabetes. Bianchetti et al [ 41 ] reported that the reduced erythrocyte membrane fluidity caused by increasing nonenzymatic glycosylation, reactive oxygen species, and lipid peroxidation may be an indicator of retinopathy of T1DM. The fluidity change of diabetic erythrocytes increases their aggregation and weakens their deformability and further leads to their metabolic disorders.…”
Section: Erythrocyte Changes In Patients With Diabetesmentioning
confidence: 99%
“…Therefore, HbA1c is an effective indicator for preventing and monitoring diabetic complication. When combined with other erythrocyte indicators such as membrane fluidity, it can monitor DR better [ 41 ].…”
Section: Erythrocyte Changes In Patients With Diabetesmentioning
confidence: 99%
“…These processes are associated with molecular motion within a lipid bilayer and activity regulation of other molecules, including membrane-bound proteins. It was reported that abnormalities in the physical properties of cell membranes may underlie the defects that are strongly linked to hypertension, stroke and other cardiovascular diseases [ 7 , 8 ], diabetes mellitus [ 9 ], and Alzheimers [ 10 ]. Therefore, studies of the relationships between fluidity and phase transitions in membranes are relevant.…”
Section: Introductionmentioning
confidence: 99%